Design and characterization of the Large-aperture Experiment to Detect the Dark Age (LEDA) radiometer systems. Issue 3 (16th May 2018) - Price, D C; Greenhill, L J; Fialkov, A; Bernardi, G; Garsden, H; Barsdell, B R; Kocz, J; Anderson, M M; Bourke, S A; Craig, J; Dexter, M R; Dowell, J; et al.
ABSTRACT: The Large-aperture Experiment to Detect the Dark Age (LEDA) was designed to detect the predicted O(100) mK sky-averaged absorption of the cosmic microwave background by hydrogen in the neutral pre- and intergalactic medium just after the cosmological Dark Age. The spectral signature would be associated with emergence of a diffuse Lyα background from starlight during 'Cosmic Dawn'. Recently, Bowman et al. have reported detection of this predicted absorption feature, with an unexpectedly large amplitude of 530 mK, centred at 78 MHz. Verification of this result by an independent experiment, such as LEDA, is pressing. In this paper, we detail design and characterization of the LEDA radiometer systems, and a first-generation pipeline that instantiates a signal path model. Sited at the Owens Valley Radio Observatory Long Wavelength Array, LEDA systems include the station correlator, five well-separated redundant dual polarization radiometers and back-end electronics. The radiometers deliver a 30–85 MHz band (16 < z < 34) and operate as part of the larger interferometric array, for purposes ultimately of in situ calibration. Here, we report on the LEDA system design, calibration approach, and progress in characterization as of 2016 January. The LEDA systems are currently being modified to improve performance near 78 MHz in order to verify the purported absorption feature.